2019
DOI: 10.1177/1077801219870608
|View full text |Cite
|
Sign up to set email alerts
|

Online Interpersonal Victimization as a Mechanism of Social Control of Women: An Empirical Examination

Abstract: Cyber space is an ever-expanding mode of perpetrating sexualized violence toward women. This article empirically examines the applicability of Susan Brownmiller’s adaptation of the theory of social control to online interpersonal victimization (OIV) against women. Multiple regression analysis identified predictors of behaviors indicative of social control among a Canadian sample. Findings suggest that the theory of social control, which has been applied to violence against women in physical space, is applicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Even without explicit calls for harassment, we argue that response videos create conditions in which harassment flourishes-a blueprint for harassment. If perpetrators of harassment often believe that their actions are justified (Blackwell, Chen, Schoenebeck, & Lampe, 2018;Jhaver, Chan, & Bruckman, 2018), and if harassment is understood as punishment for norm violation (Crockett, 2017;Hill & Johnson, 2020), then these videos draw upon social norms shared by a networked audience and the technical affordances of YouTube to explain to the audience not only why the target is wrong, but why they are immoral and why harassing them would be justified.…”
Section: Is the Relationship Between Amplifiers And Harassment?mentioning
confidence: 99%
See 1 more Smart Citation
“…Even without explicit calls for harassment, we argue that response videos create conditions in which harassment flourishes-a blueprint for harassment. If perpetrators of harassment often believe that their actions are justified (Blackwell, Chen, Schoenebeck, & Lampe, 2018;Jhaver, Chan, & Bruckman, 2018), and if harassment is understood as punishment for norm violation (Crockett, 2017;Hill & Johnson, 2020), then these videos draw upon social norms shared by a networked audience and the technical affordances of YouTube to explain to the audience not only why the target is wrong, but why they are immoral and why harassing them would be justified.…”
Section: Is the Relationship Between Amplifiers And Harassment?mentioning
confidence: 99%
“…Feminist scholars situate online harassment within a broader landscape of misogyny and sexual violence (Henry & Powell, 2015; Jane, 2014). While diverse populations experience harassment, women, especially women of color and queer women, are far more likely to experience serious online harassment like stalking (Lenhart et al, 2016; Vitak et al, 2017), which discourages marginalized populations from participating online (Hill & Johnson, 2020; Moloney & Love, 2018). Sarah Banet-Weiser and Kate Miltner (2016) refer to “networked misogyny” as “an especially virulent strain of violence and hostility towards women in online environments.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of harassment are myriad. People who experience harassment may experience depression, anxiety, emotional distress, suicidal ideation, self-harm, stress, and increased fear (Hill and Johnson 2019; Veletsianos et al 2018). Others have lost their jobs, social or economic status, personal relationships, and professional opportunities due to harassment (Sobieraj 2018).…”
Section: Risky Researchmentioning
confidence: 99%
“…International organizations warn us about the impacts of this type of violence, which range from harm to a person's reputation through psychological disorders to self-injury and suicide in extreme circumstances (Khoo 2021). Previous studies have found that survivors of this type of violence are more likely to be absent from schools and workplaces, resign from their jobs or studies, and avoid social events (Hill and Johnson 2019). Additionally, the most common response by women and LGBTQI+ in order to face this expression of violence is to reduce their online activities by disconnecting from social networks or self-censoring; in this way, gender-related digital violence (GRDV) is also impacting women's political participation, freedom of expression, and mobilization (Khoo 2021).…”
Section: Introductionmentioning
confidence: 99%